Coinoculation of diazotrophic bacteria in upland rice, cultivar BRS Esmeralda - Guimarães, Salomão Lima; Ormay, Phellype da Silva (Seven Editora, 2023)
This study aimed to evaluate the efficiency of associative bacteria inoculation and rhizobia coinoculation in upland rice. The experiment was conducted in a greenhouse. The experiment was conducted in a completely randomized design, containing seven treatments: commercial inoculant (CI), coinoculation with four rhizobia strains: MT16, MT23, MT08, MT15 and two controls (nitrogen - 50 mg dm-3 of nitrogen in the form of urea, and absolute without nitrogen and without inoculation), with 5 replications, totaling 35 experimental units. DOI:https://doi.org/10.56238/alookdevelopv1-162